2022
DOI: 10.3390/healthcare10040740
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorders, Bruxism, Perceived Stress, and Coping Strategies among Medical University Students in Times of Social Isolation during Outbreak of COVID-19 Pandemic

Abstract: The COVID-19 pandemic caught universities along with their students off-guard, enforcing online education. Fear of the unknown, disinformation, and isolation resulted in an increased stress level in the entire population. Medical university students are particularly endangered with high stress levels and developing TMD. Temporomandibular disorders (TMD) are of multifactorial etiology, and manifest with jaw dysfunction, masticatory muscle tension or pain, as well as headache. Though bruxism can act as an exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
1
11
0
2
Order By: Relevance
“…The social isolation, which is one of the psychological factors, negatively affects both physical and mental health (30,31). In the study of Saczuk et al (32), it was observed that the findings of TMD and bruxism increased with social isolation. One of the important results of the current study was that videos containing bruxism increased with the COVID-19 pandemic process.…”
Section: Discussionmentioning
confidence: 99%
“…The social isolation, which is one of the psychological factors, negatively affects both physical and mental health (30,31). In the study of Saczuk et al (32), it was observed that the findings of TMD and bruxism increased with social isolation. One of the important results of the current study was that videos containing bruxism increased with the COVID-19 pandemic process.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo observacional transversal conduzido com estudantes de odontologia de uma universidade de Brasília encontrou sintomas de DTMs no período inicial da pandemia, além de relatarem uma associação positiva entre comportamentos orais, como apertar e ranger os dentes, com DTMs (Medeiros et al, 2020). Outro estudo transversal realizado com estudantes de medicina encontrou alta prevalência de sinais e sintomas de DTMs e bruxismo durante a pandemia (Saczuk et al, 2022). Estes achados estão de acordo com o levantamento da presente pesquisa, que teve amostra composta em sua maioria por estudantes com relatos da influência dos hábitos orais na dor.…”
Section: Discussionunclassified
“…Está estabelecido na literatura que ansiedade, depressão, estresse percebido e estados de humor são fatores de risco importantes para o desenvolvimento ou cronicidade das DTMs (de La Torre Canales et al, 2018;Fillingim et al, 2013;Fillingim et al, 2018;Greene & Manfredini, 2021;Kindler et al, 2012;Manfredini et al, 2009;Yap et al, 2021;Yap et al, 2022). A pandemia de coronavírus tem o potencial de causar efeitos significativos no estado psicoemocional dos indivíduos podendo se relacionar diretamente com o surgimento de DTMs (Carrillo-Diaz et al, 2022;Cerqueira et al, 2021;Emodi-Perlman et al, 2020;Saczuk et al, 2022;).…”
Section: Introductionunclassified
“…In the current study, statistically significant positive correlation between total stress score and the overall maladaptive coping score was found (Figure 2). Correspondingly, Saczuk et al (35) found that the higher the PSS-10 score, the less frequently problem-focused coping strategies, such as planning, active Coping, seeking Instrumental Support, and positive reframing, or emotion-focused strategies, i.e., acceptance, humor, religion, and seeking emotional support, were chosen (negative correlation). On the contrary, they discovered that a high PSS-10 score increases the frequency of choosing emotion-focused coping, such as self-blaming and venting, or avoidant coping, such as selfdistraction, substance use, and behavioural disengagement or denial (positive correlation).…”
Section: Figure (1)mentioning
confidence: 99%